When the machine stopped : - Holland, Max (Harvard Business School Press, 1989)
From the careful craftsmanship of machine tools to the ingenious crafting of a leverage buyout and the intricacies of a bitter trade dispute, Holland tells the life-and-death story of a machine tool company called Burgmaster. When the Machine Stopped speaks volumes on innovation, foreign and domestic competition, employee relations, leveraged buyouts, U.S. trade policy, and more. "Anyone who wants to understand American business must read When the Machine Stopped-Holland has written the best business book in years."-Chicago Tribune "Fascinating-the fate of Burgmaster and its brethren is crucial to the U.S.